Blastic Mantle Cell Lymphoma of the Gastroesophageal Junction: A Unique Presentation and Literature Review - Ahmed M. Ahmed; Sima Vossough (Case Reports in Gastroenterology, 2021)
Although vast, the medical literature is deficient in reports of gastroesophageal junction (GEJ) involvement of mantle cell lymphoma (MCL). We present the unique case of a 76-year-old male who presented with worsening dysphagia, weight loss, and heartburn and who was found to have blastic variant of MCL in the GEJ. He had undergone extensive workup in the past for an ulcerative, gastric/GEJ lesion, found on four separate esophagogastroduodenoscopies (EGDs) and two esophageal ultrasounds, whose biopsies were repeatedly negative for malignancy. On admission, physical examination and labs were unremarkable, but computed tomography showed an irregular mass involving the GEJ. EGD on admission showed a large friable, ulcerated lesion with heaped-up margins involving the GEJ whose biopsies showed histological and immunohistochemical (IHC) findings consistent with blastic MCL. A bone marrow biopsy showed minimal involvement (<5%) of CD5+/CD23+ B cells and was negative for both cyclin D1 and t(11;14). The biopsy of the lesion was diffusely infiltrated by atypical lymphocytes with prominent nucleoli and IHC stains positive for CD20, cyclin D1, BCL-2, and BCL-6 as well as a Ki-67 proliferative index >90%, all consistent with blastic MCL, a rare and aggressive subtype of MCL. He was started on guideline-based chemoimmunotherapy as he was not a candidate for stem cell transplantation. Repeat imaging 1 year later showed improvement of the mass, with negative endoscopic biopsies for lymphoma. This case provides additional distinct features to the various clinical presentations associated with this rare proliferative disorder, thereby enhancing the medical literature on MCL.